FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI SEDIAAN FOOTSPRAY ANTI BAU KAKI EKSTRAK TEH HITAM (Camellia sinensis) DAN DAUN JAMBU BIJI (Psidium guajava L.) - Shalsadila, Rifani; Nuryanti, Mega; Siahaan, Nurbaiti Fentiani; Nurkamal, Elsa; Farhan, Dicky; Purwaeni (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2024)
Increased release of apocrine infected by bacteria during the decay process will result in foot odor or bromhidrosis. Foot odor is caused by skin microbes. Some of the bacteria that cause foot odor are Staphylococcus epidermidis and Staphylococcus aureus. Black tea and guava leaves are natural ingredients that contain antibacterial compounds, namely flavonoids, saponins, tannins and alkaloids. The purpose of this study was to formulate footspray preparations from extracts of black tea and guava leaves and to determine the antibacterial activity of each formulation. This study uses an experimental method. Extracts of black tea and guava leaves are produced from the maceration extraction process, then the resulting extract is formulated into footspray with various concentrations. Footspray preparations were tested for evaluation of physical preparations and tested for antibacterial activity of Staphylococcus epidermidis and Staphylococcus aureus by the paper disc method. The results showed that black tea and guava leaf extracts could be formulated as active substances in footspray preparations which had antibacterial activity which was indicated by the presence of clear zones in formulas 1, 2 and 3. However, in the control formula there was no antibacterial activity which was indicated by the absence of clear zone.